2012
DOI: 10.1097/pec.0b013e3182768a86
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Nitrous Oxide Versus Intravenous Ketamine for Laceration Repair in Children

Abstract: Nitrous oxide inhalation was preferable to injectable ketamine for pediatric patients because it is safe, allows for a faster recovery, maintains sufficient sedation time, and does not induce unnecessarily deep sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Lee et al 16 provided further support of the efficacy of N 2 O. Patients were randomized to 50% to 70% N 2 O or ketamine 2 mg/kg IV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al 16 provided further support of the efficacy of N 2 O. Patients were randomized to 50% to 70% N 2 O or ketamine 2 mg/kg IV.…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies provided data comparing sedatives and analgesics via the extravascular route to placebos or comparator agents and the sedatives and analgesics were noted to be efficacious. [3][4][5][6][7][8][9][10][11][12][13][14][15][16] Two studies compared combination therapy using PO midazolam. 17,18 It is difficult to compare the findings of these studies given the variability of sample size in the studies as well as the variety of agents, dosage forms, and dosing used.…”
Section: Discussionmentioning
confidence: 99%
“…Two RCTs compared the effect of N 2 O with that of ketamine or fentanyl (22,23) and described equivalent effect significantly more rapidly than morphine alone (17,21,39). However, two of the RCTs showed that pain reduction was comparable after 30 min (24,25).…”
Section: Other Analgesicsmentioning
confidence: 99%
“…Based upon the recent literature, N 2 O may be poised for something of a comeback in the acute care setting [80,155,156,[164][165][166][167]. The agent is well known, self-administered, safe, and at least moderately effective.…”
Section: Nitrous Oxide (N 2 O)mentioning
confidence: 99%
“…Special scales that have been well described in the literature can be used for validated pain assessment (and thus enable appropriate analgesia provision) [79][80][81][82]. The lack of IV access can also be problematic.…”
Section: Pay Special Attention To Pain Care At the Extremes Ofmentioning
confidence: 99%